SIFAT MEKANIK BIONANOKOMPOSIT FILLER NANOPARTIKEL BIOMASS KULIT ROTAN METODE INJEKSI MOLDING - siti nikmatin (Jurnal Biofisika, 2013)
Rattan  biomass  is  one  of  the  agricultural  waste  that  can  be  used  as  a  source  of cellulose  nanoparticle.  To  produce  cellulose  nanoparticle  bark  rattan  that  is  low density,  good  mechanical  properties,  natural  resources  and  renewable  resources needed a new method of development nanotechnology using hummer mill methods. The  purpose  of  this  study  is  synthesis  and  mechanical  properties  of bionanocomposite  reinforce  cellulose  nanoparticle  bark  rattan  used  injection moulding.  Cellulose  nanoparticle  is  made  with  mechanical  systems  (milling  and shakers) in size 75 μm and hummer mill t =30 minute. PSA test results produced a maximum particle size of 25.6 nm (number distribution commulant method) at the t   =30 minute. Meanwhile, the hardness and impact strength of bionanocomposite show 79.9 HRR and 67.7 J/m.